Uncovering the apocalypse : narratives of collapse and transformation in the 21st century Fin de Siècle - Carstens, Johannes Petrus (Delphi) (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)-- Stellenbosch University, 2013.